Social Policy, Food Security, and Educational Motivation: Analyzing the Implementation of the Free Nutritious Meal Program in Urban Indonesia - Zul Fadli; Imran Ismail; Zulfachry Zulfachry (Universitas Pattimura, 2026)
This study examines the implementation of Indonesia’s Free Nutritious Meal (MBG) Program as a national social policy aimed at strengthening children’s food security and improving educational motivation in urban settings, focusing on Panakkukang District, Makassar City. The research aims to evaluate the operational mechanisms of the MBG program in urban schools, assess its effects on students’ learning motivation, and identify social–institutional factors shaping policy effectiveness. A literature-informed field simulation design was employed, integrating systematic review findings, policy document analysis, and secondary data interpretation to construct an evidence-based model of implementation dynamics. Findings indicate that MBG delivery follows a multi-actor governance pattern involving local authorities, schools, parents, and community groups, producing positive impacts on student concentration, attendance, and classroom engagement, particularly among low-income households. Beyond nutritional gains, the program fosters social inclusion, strengthens school–community relations, and enhances intrinsic and extrinsic learning motivation, though sustainability challenges persist related to coordination, food quality, and funding. The study’s novelty lies in applying simulation-based inquiry to an emerging welfare policy and conceptualizing MBG as a hybrid model linking food security, educational welfare, and community-based protection. The research contributes to sociological scholarship by advancing theoretical understanding of school-based social policy and offering evidence-informed recommendations to strengthen welfare interventions in urban Indonesia.